2021
DOI: 10.1007/s12083-021-01248-6
|View full text |Cite
|
Sign up to set email alerts
|

Efficient topology control of blockchain peer to peer network based on SDN paradigm

Abstract: Blockchain allows to securely store, using cryptography functions, validated transactions and other data across its peer to peer (P2P) network. This P2P network is generated and maintained by the participating peers in a distributed manner through peer discovery, neighbor selection and managing inbound/outbound connections. As these tasks require extra consumption of network bandwidth, energy, memory and CPU usage, resource-limited devices may not support inherent blockchain applications. Further, changes in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…This method leads to excessive dependence on the nodes that have the shortest total propagation time, which can reduce node performance. Deshpande et al [44] proposed a centralized solution. This solution utilizes the principles of Software-Defined Networking (SDN) to reduce the excessive overhead in managing a distributed network for blockchains.…”
Section: Baniata and Anaqrehmentioning
confidence: 99%
“…This method leads to excessive dependence on the nodes that have the shortest total propagation time, which can reduce node performance. Deshpande et al [44] proposed a centralized solution. This solution utilizes the principles of Software-Defined Networking (SDN) to reduce the excessive overhead in managing a distributed network for blockchains.…”
Section: Baniata and Anaqrehmentioning
confidence: 99%
“…Some bootstrap nodes complete the otherwise empty peers' lists. The remainder is progressively filled by peers identified using a distributed peer discovery method, such as Peers' list Exchange Protocol (PEX) and a modified Kademlia DHT protocol [22].A blockchain system must quickly distribute freshly created blocks to maintain a consistent global picture independent of the network's representation. A routing protocol may not be needed, but a synchronization protocol.…”
Section: P2p Networkmentioning
confidence: 99%
“…Deshpande et al [83] used a centralized approach, as shown in Figure 7, to reduce the overhead incurred by the distributed network management of a vanilla blockchain. Dedicated servers generated the P2P topology and assigned neighbors to each peer.…”
Section: P2p Topology Optimizationmentioning
confidence: 99%